Model Satisfaction Users Measurement of Academic Information System Using End-User Computing Satisfaction (EUCS) Method - Nur Aeni Hidayah; Elvi fetrina; Alvali Zaqi Taufan (Applied Information System and Management (AISM), 2020)
As concrete steps in order to realize the vision and mission of an organization or educational institution is to implement the system of academic information. The one factor that influences the success of the academic information system is the satisfaction of users.  The problems in the user satisfaction are also issues that cannot be denied and continue to be studied. In consequently, having measurements related to user satisfaction is required. This research is done to see how the user satisfaction of the existing system has been implemented and to know what factorshas influenced the system. The method used in this study is a quantitative method using the End User Computing Satisfaction (EUCS) model whereas 255 respondents are chosen as the sample for the study. The purposive sampling technique is usedand the PLS-SEM approach with tools Smart PLS 3.0 is used for analyzing the data.  This research consists of 7 hypotheses and 8 variables, namely Content, Accuracy, Format, Timeliness, Ease of Use, System Reliability, System Speed and End-User Satisfaction. The research finds out that the current level of end-user satisfaction is in satisfied level. Inferentially, of the 7 hypotheses tested, 2 of them were rejected and the other 5; Accuracy, System Reliability, Timeliness, Content and System Spee;are accepted.Through this research, it is hoped that later it could be used as a practical consideration and theoretical study in thefuture.